The Impacts of the Coronavirus 2019 (COVID-19) Pandemic Situation on Human Resource Management of Hotel Businesses in Mueang District, Chiang Rai Province - Khemma-akrajet, Atcharaphat; Benchakorn, Benchawan (Parichart Journal, 2024)
This study was to investigate the impact of the 2019 coronavirus outbreak on 3-4 star hotels in Muang District, Chiang Rai Province and study how to manage human resources under those circumstances. Here, 5 out of 193; 3-4 star hotels were selected as the samples for the following three reasons: 1) 3-4 star hotels have had excellent service standards and could be good representatives of the mid- to high-end hotel segment, 2) the selection of 5 locations was because the data collection period was during the COVID-19 outbreak, and 3) selecting this sample group saved time and utilized limited resources. Finally, having specific information from these hotels could be used to effectively plan strategies in developing and raising the service standards of hotels in the same group. Open-ended structured interviews were used as an instrument in this study. The study found that the impacts arising from the COVID-19 outbreak included 1) business results area, 2) manpower area, and 3) expenses area. Moreover, the results have shown the guidelines of human resource management which the hotels applied to deal with the difficult situations. These involved 1) developing employees' skills to have a variety of skills (multi-skills), 2) reducing costs, such as saving energy, using resources most productively, and reducing wages of some employees, 3) utilizing reserve funds to keep the business running during difficult times., and finally 4) changing working styles to suit the situation.